The impact of the Eurozone sovereign debt crisis on bond fund performance persistence: Evidence from a small market. (28th October 2016) - Leite, Paulo; Faria, Orlando; Armada, Manuel Rocha
ABSTRACT: We evaluate the impact of the Eurozone sovereign debt crisis on the performance and performance persistence of a survivorship bias-free sample of bond funds from a small market, identified as one of the most affected by this event, during the 2001–2012 period. Besides avoiding data mining, we also introduce a methodological innovation in assessing bond fund performance persistence. Our results show that bond funds underperform significantly both during crisis and non-crisis periods. Besides, we find strong evidence of performance persistence, for both short- and longer-term horizons, during non-crisis periods but not during the debt crisis. In this way, the persistence phenomenon in small markets seems to occur only during non-crisis periods and this is valuable information for bond fund investors to exploit.